Upaya Kyai dalam Harmonisasi Rumah Tangga Alumni : Studi Kasus Di Kec. Gading - M Hasan Zinul Abidin; Imam Syafi’i R; Abd. Hannan (Pusat Riset dan Inovasi Nasional, 2025)
Marriage in Islam is a sacred institution aimed at forming a family that embodies sakinah, mawaddah, and rahmah, while also serving as a legitimate and responsible means to fulfill biological needs. In the socio-religious context, religious figures such as kyai play a significant role, particularly in guiding the community to maintain household harmony. This study explores the role of kyai in promoting household harmony among Islamic boarding school alumni in Gading District, an area where the spiritual bond between kyai and santri remains strong. These alumni often face various challenges in their domestic lives, including differences in perspectives with their spouses and shifts in social values in the modern era. In such circumstances, kyai serve as spiritual advisors, counselors, and mediators who offer solutions based on Islamic values and local wisdom. This research aims to identify the types of guidance provided by kyai, as well as the supporting factors and obstacles they encounter in fulfilling their roles. The findings are expected to enrich scholarly discourse in the field of socio-religious studies and offer practical insights for religious leaders to strengthen their roles as agents of family harmony amid the complexities of modernization.